Capacity Building of ASHA at the Monthly Meeting Platforms IN PHC and CHC in Uttar Pradesh, India - Tripathy, Tridibesh; Das, Shankar; Tripathy, Anjali; Dwivedi, Rakesh; Gautam, Mohini (Selected Topics in Humanities and Social Sciences Vol. 2, 2021)
Introduction: The engagement of women community health workers has been recognized as one key strategy to tackle the emergent shortage of health workers in developing countries. The ASHAs are instituted by the state as part of National Rural Health Mission of the Government of India for the grassroots health care delivery. The capacity building initiatives and empowerment of the local women are crucial for effective health care delivery of large section of rural population. The current study explores some of the crucial variables of the capacity building initiatives at the monthly meeting platforms at CHC/PHC in the state of UP. Research methodology: A total of four districts of Uttar Pradesh were selected purposively for the study and the data collection was conducted in the villages of the respective districts with the help of a pre-tested structured interview schedule with both close-ended and open-ended questions. In addition, in-depth interviews were also conducted amongst the ASHAs and a total 250 respondents had participated in the study. Results: A large majority (90 percent) of the ASHAs attended and benefitted from the monthly meetings at various PHCs in their respective districts. The total duration of these meetings varied from 2-3 hours each in different districts and mainly the agenda of these meetings were review of daily work, training and problem solving. Additionally various other topics were covered in the meetings such as cord care and new-born care; however certain topics such as interpersonal skills, gender and equity were not dealt adequately. Difficulty and poor attendance in the meetings were also reported from Banda District of Bundelkhand region due to inaccessibility, challenges in travelling and frequent rescheduling of the meetings. Primarily the Health Education Officers were the leading facilitators of these meetings in the four districts. The benefits of these meetings were cited by the ASHAs as those built their level of confidence while working in the community and the inputs also enhanced the required level of knowledge on different health issues. At the same time, they also reported that their counseling skills as well as the quality of home visits had improved. Conclusions: The process of capacity building of ASHAs in the monthly meeting platforms could be considered as a significant strategy in developing the community health workforce. These meetings and training platforms are optimally utilized to improve the level of motivation, confidence, work skills, quality and quantity of their home visits. The meetings are more effective if the areas such as regular guidance, work related problem solving, record keeping and documentation of activities were discussed frequently.